2016
DOI: 10.1038/srep26985
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological profiles of sputum and gastric juice aspirates in Cystic Fibrosis patients

Abstract: Gastro-Oesophageal Reflux (GOR) is a key problem in Cystic Fibrosis (CF), but the relationship between lung and gastric microbiomes is not well understood. We hypothesised that CF gastric and lung microbiomes are related. Gastric and sputum cultures were obtained from fifteen CF patients receiving percutaneous endoscopic gastrostomy feeding. Non-CF gastric juice data was obtained through endoscopy from 14 patients without lung disease. Bacterial and fungal isolates were identified by culture. Molecular bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 42 publications
(54 reference statements)
3
40
0
2
Order By: Relevance
“…In CF patients, gut and lung microbiota are distinct from those of healthy subjects, and disease progression is associated with microbiota alterations (Madan et al, 2012;Stokell et al, 2015;Nielsen et al, 2016). Moreover, the bacterial abundances at both sites are highly correlated and have similar trends over time (Madan et al, 2012), especially regarding Streptococcus, which is found in higher proportion in CF stools, gastric contents, and sputa (Al-Momani et al, 2016;Nielsen et al, 2016). Moreover, CF patients with a documented intestinal inflammation exhibit a higher Streptococcus abundance in the gut , suggesting the GLA's involvement in intestinal inflammation.…”
Section: Chronic Respiratory Diseasesmentioning
confidence: 99%
“…In CF patients, gut and lung microbiota are distinct from those of healthy subjects, and disease progression is associated with microbiota alterations (Madan et al, 2012;Stokell et al, 2015;Nielsen et al, 2016). Moreover, the bacterial abundances at both sites are highly correlated and have similar trends over time (Madan et al, 2012), especially regarding Streptococcus, which is found in higher proportion in CF stools, gastric contents, and sputa (Al-Momani et al, 2016;Nielsen et al, 2016). Moreover, CF patients with a documented intestinal inflammation exhibit a higher Streptococcus abundance in the gut , suggesting the GLA's involvement in intestinal inflammation.…”
Section: Chronic Respiratory Diseasesmentioning
confidence: 99%
“…The GI microbiome of CF patients has reduced richness and diversity beginning in early childhood (2 years) and continuing until late adolescence (17 years) 163 . Other changes that may affect the overall clinical outcome include an increased abundance of P. aeruginosa in the gastric juice of CF patients, and markedly lower abundance of normal gut bacteria ( Bacteroides , Faecalibacterium ) in digestive tract samples from CF patients compared with non‐CF individuals 164 . Notably, the severity of CFTR dysfunction was related to dysbiotic faecal bacterial profiles, with an increased abundance of deleterious species ( Escherichia coli , Eubacterium biforme ) and reduction in normal species ( F. prausnitzii , Bifidobacterium spp., Eubacterium limosum ) 165 .…”
Section: The Role Of the Microbiome In Cfmentioning
confidence: 99%
“…163 Other changes that may affect the overall clinical outcome include an increased abundance of P. aeruginosa in the gastric juice of CF patients, and markedly lower abundance of normal gut bacteria (Bacteroides, Faecalibacterium) in digestive tract samples from CF patients compared with non-CF individuals. 164 Notably, the severity of CFTR dysfunction was related to dysbiotic faecal bacterial profiles, with an increased abundance of deleterious species (Escherichia coli, Eubacterium biforme) and reduction in normal species (F. prausnitzii, Bifidobacterium spp., Eubacterium limosum). 165 Gut microbiota dysbiosis in CF children (o3 years old) has also been linked to significantly altered lipid metabolism, including depleted capacity for overall fatty acid biosynthesis and increased capacity for degrading anti-inflammatory SCFAs, particularly butyrate and propionate, 166 which may lead to increased risk of developing allergic responses in the lungs.…”
Section: The Role Of the Microbiome In Cfmentioning
confidence: 99%
“…In comparison, non CF gastric juice samples revealed a higher diversity. The stomach microbiome in patients with CF may act as a potential pathogen reservoir and the aerodigestive microbiome warrants further research as it may impinge on the pathophysiology of CF [27]. Bile acid aspiration is a comorbidity factor linked to many lung diseases which could plausibly shape the lung microbiome and promote the colonisation of Pa in CF patients.…”
Section: Lung Diseasesmentioning
confidence: 99%